Evaluation of remediation techniques in soils affected by residual contamination with heavy metals and arsenic. (15th April 2017) - García-Carmona, M.; Romero-Freire, A.; Sierra Aragón, M.; Martínez Garzón, F.J.; Martín Peinado, F.J.
Abstract: Residual soil pollution from the Aznalcóllar mine spill is still a problem in some parts of the affected area, today converted in the Guadiamar Green Corridor. Dispersed spots of polluted soils, identified by the absence of vegetation, are characterized by soil acid pH and high concentrations of As, Pb, Cu and Zn. Ex situ remediation techniques were performed with unrecovered soil samples. Landfarming, Composting and Biopiles techniques were tested in order to immobilize pollutants, to improve soil properties and to promote vegetation recovery. The effectiveness of these techniques was assessed by toxicity bioassays: Lactuca sativa L. root elongation test, Vibrio fischeri bioluminescence reduction test, soil induced respiration test, and Eisenia andrei survival and metal bioaccumulation tests. Landfarming and Composting were not effective techniques, mainly due to the poor improvement of soil properties which maintained high soluble concentrations of Zn and Cu after treatments. Biopile technique, using adjacent recovered soils in the area, was the most effective action in the reduction of soil toxicity; the improvement of soil properties and the reduction in pollutants solubility were key to improve the response of the tested organisms. Therefore, the mixture of recovered soils with polluted soils in the areas affected by residual contamination is considered a more suitable technique to reduce the residual pollution and to promote the complete soil recovery in the Guadiamar Green Corridor. Highlights: Residual soil pollution in Guadiamar Green Corridor is still a problem 18 years after contamination. Soil toxicity bioassays were key tools for the assessment of remediation techniques applied. Landfarming and Composting were not effective due to the high soluble concentrations of Zn and Cu after treatment. Biopiles, using recovered soils in the area, were the most effective treatment for soil remediation.